Integratori e analgesia: caduta e ascesa di un antiossidante, il resveratrolo - Integrators and analgesia: fall and raise of an antioxidant: resveratrol - Maria Luisa Sotgiu (Publiediting, 2015)
Resveratrol, a natural polifenol widely found in the red wine, is an antioxidant to which several other beneficial properties have been improperly attributed. Recently the mechanisms underlying its antioxidant effect, have been indagated. It has been found that for its inhibitory action on the microglia activation, the resveratrol attenuates the development of opioid tolerance. Therefore it may be part of the strategy to contrast this phenomenon.